The Antioxidant Activity, Antibacterial Assay, and the Application of Turmeric (Curcuma domestica) Crude Extract with Various Solvents - Fiane de Fretes; Rosiana Eva Rayanti; Agung Rimayanto Gintu (Future Science, 2023)
Turmeric (Curcuma domestica) was one of the herbal resources in Indonesia commonly applied as spices, herbal medicines also cosmetics. This study aimed to extract the chemicals from Turmeric using several solvents and then characterize each extract. The physicochemical and Biochemical characterization of each Turmeric extract showed that the crude extracts have a strong antibacterial effect against digestive bacteria and respiratory and skin bacteria. The antioxidant activity belongs to high levels also the Sun Protection Factor (SPF) ability of each extract showed belongs to Ultra Protection levels. Based on those results than concluded that Turmeric potentially applied as Herbal medicine and Cosmetics in Indonesia.